Practices of Top Performing Science Secondary Schools in Baguio City - Nicer, Philip Julius (SEAMEO QITEP in Science, 2023)
The progress of any nation has been associated with its scientific and technological expansion. This suggests that science plays a momentous part in the economic, technological, administrative, and ecological improvement of any nation-state because science has saturated all aspects of human existence. The study sought to identify science practices of the school participants that led to their high performance in various science-related activities. This study identified the profile of the school and its stakeholders, including their material resources and practices/methods for achieving high levels of success in science-related activities. Mixed method research was employed in processing the gathered data. It has been found that: (1) positive atmosphere; (2) learner-centred activities; (3) professional development; and (4) strong linkages generally contributed to the high performance of the schools in science-related activities. As a recommendation, a more contrived and intricate manner of assessing learning among student participants leaning towards their high performance in science-related activities and competition should be made.